Role of the dentist in the prevention of periodontal diseases and edentulism (Research, Society and Development, 2023)
In order for the dentist to act with his patients and protect his oral health, it is worth remembering that prevention is only possible through awareness, in which he has a fundamental role, because he is a safe source and has knowledge necessary and correct ones training and methods to achieve them in the best possible way, which contributes to disease prevention. The contribution of the dentist to the improvement of this situation is based on attitudes of trust and oral health care of the patient who in most cases is afraid of this professional or does not have financial condition to bear the costs of the procedures. Thus, this work aims to present the role of the dentist in the prevention of periodontal diseases and edentulism. The search for the studies was carried out in the electronic databases: NCBI/PubMed, SciELO and Lilacs - Bireme. The inclusion criteria were: articles available in full, in Portuguese and English, in the period 2017 to 2022 with free access and that had affinity with the theme. Preventive dental techniques are very simple, easy to understand and easy, but should be practiced every day. Dental hygiene, balanced feeding, correct use of fluoride and semiannual dental follow-up are the most important tips for maintaining oral health. A responsible and professional clinical evaluation by a dentist is an important step in keeping your mouth healthy.